An Invariable to Rotation Data Hiding Scheme for Semi-Fragile Blind Watermark - Amine, Khaldi (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2020)
An invariant to rotation watermarking approach is proposed for the purpose of improving the security of digital images. The proposed digital watermark approach is invariable to rotation and guarantees the integrity of the inserted mark. The size of the resulting image is identical to the original image and the process guarantees acceptable transparency. This approach evolves both in the frequency and the spatial domain. Specifically, the proposed scheme processes the JPEG images by adapting its structure to the frequency domain by modifying the DCT coefficients of the image. This scheme is also adaptable to BMP images by adjusting these parameters for an LSB modification of the colorimetric values of the image. Moreover, during the extraction, the structure of our scheme organizes itself according to the orientation of the processed image. Based on the experiment conducting with eight substitution processes, we concluded that the substitution of four bits gives a great capacity of insertion, while guaranteeing an acceptable transparency for the insertion of text. However, a substitution of one bit only is recommended for the insertion of an image. This reduces the capacity, but guarantees transparency of the watermarking process.